AN ANALYSIS OF DIRECTIVE ILLOCUTIONARY ACTS IN THE DIVERGENT MOVIE 2014 BY DOUGLAS WICK AND LUCY FISHER - ZENI NOVITASARI; Yulia Nugrahini Nugrahini; Erna Dwinata (STKIP PGRI TULUNGAGUNG, 2016)
This thesis is aimed at describing forms and meanings ofutterances based on Vandervekenâ€™s theory by using descriptive method.Yule (1996 : 54) said that â€œdirectives are those kinds of speech act thatspeaker use to get someone else to do something. They express what thespeaker wants. They are commands, orders, request, suggestionâ€.Incollecting the data, the researcher follows three stages. Those are dataselection, data collection, and data classification. The selection stage wasdone by searching the movie script as the data source, the data collectioncovers collecting the data from utterance in the movie script, and the dataclassification includes gathering utterances which contain DirectiveIllocutionary Act. In analyzing the data, researcher follows several stages.They are: founding categorizing, describing, and qualifying theutterances found in the data.From all of the utterances, there are seventypes of Directive Illocutionary Acts found in utterances, those are:Asking, Commanding, Requesting, Suggesting, and Begging. From thoseforms of Directive Illocutionary Act, Suggesting has the highestfrequency of use among others, that is twelve times, the Begging has thelowest frequency of use among others, that is one times.To describe themeaning of the analysis the researcher used six component ofVanderveken and the meaning of the utterances is mostly suggesting.Based on the meanings of the Illocutionary Act in utterances, most of thepoint of Illocution is that the speaker ask to the hearer to do something;most of the mode of achievement is that the hearer can give the answer orexplanation from the speaker question or command; the propositionalcontent of the utterances is mostly showing that the speaker ask to thehearer to answer or to doing what the speaker want; most of thepreparatory condition of the utterances is that the speaker believes thatthe hearer can achieve what the speaker wants; most of the sincerity ofcondition of the utterances is that the speaker really hopes to the hearerto conduct his will; and the degree of strength of the utterances is mostlyshowing that the speaker seriousness to get respond from the hearer.Key Words : Directive Illocutionary Acts, Divergent Movie 2014